Influence of localised igneous activity on cleat dawsonite formation in Late Permian coal measures, Upper Hunter Valley, Australia - Golab, Alexandra N.; Carr, Paul F.; Palamara, Daniel R. (International journal of coal geology, 2006)
Stable ( δ 13C and δ 18O) and radiogenic 87Sr/ 86Sr isotopic data have been used to investigate the origin of cleat dawsonite (NaAlCO 3(OH) 2) in the Late Permian Wittingham Coal Measures of the Upper Hunter region in the Sydney Basin, New South Wales. The δ 13C PDB values have a narrow range (− 1.7‰ to + 2.4‰), with an average of + 0.3‰, suggesting a magmatic source for the carbon. In contrast, δ 18O SMOW values have a wide range (+ 13.6‰ to + 19.8‰), and decrease systematically with decreasing distance from a major intrusion. This systematic variation reflects establishment of localised hydrothermal cells. Water–rock interaction between fluids associated with these hydrothermal cells, and Rb-poor volcaniclastic detritus in the coal measures, produced mantle-like 87Sr/ 86Sr (0.705032 to 0.706464) in the dawsonite.